1999
DOI: 10.1046/j.1469-8137.1999.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of ectomycorrhizal fungi in self‐regenerating boreal Pinus sylvestris forests studied by comparing mycobiont diversity on seedlings and mature trees

Abstract: Seedlings and old trees of Scots pine in self-regenerating, old, virgin boreal forest in northern Sweden were compared in terms of the species composition of their associated ectomycorrhizal (EM) fungi. The natural regeneration of seedlings was mimicked by annual seeding for 10 yr (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995) in intact field vegetation at three sites. In 1995, all seedlings were harvested, and 171 were examined for mycorrhizas. Twenty-five soil cores were taken in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 47 publications
(58 reference statements)
6
118
1
3
Order By: Relevance
“…Unfortunately we do not have sporocarp records for our site, and an extensive above and below ground sampling effort would be required adequately to answer the question. We can however, compare our data with those of Jonsson et al (1999) who worked in virgin Scots pine forest in northern Sweden. They took 15 soil cores and counted 1978 ectomycorrhizas to characterise the EcM fungal community on the mature trees at one of their sites.…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately we do not have sporocarp records for our site, and an extensive above and below ground sampling effort would be required adequately to answer the question. We can however, compare our data with those of Jonsson et al (1999) who worked in virgin Scots pine forest in northern Sweden. They took 15 soil cores and counted 1978 ectomycorrhizas to characterise the EcM fungal community on the mature trees at one of their sites.…”
Section: Discussionmentioning
confidence: 88%
“…Our studies revealed that the distribution of the frequencies of the fungal species in this community was typical, with a few abundant species and many species of significantly lower abundance (Kårén & Nylund, 1996;Gehring et al, 1998;Jonsson et al, 1999;Mahmood et al, 1999;Stendell et al, 1999;Grogan et al, 2000;Taylor, 2002). Cenococcum geophilum was the most frequently encountered species, both as hyphae in the F-layer and as a root colonist.…”
Section: Discussionmentioning
confidence: 99%
“…that represent a range of ecological characteristics in nature. Cenococcum geophillum and Piloderma bicolor are considered multi-stage fungi (Visser 1995, Bradbury et al 1998, Jonsson et al 1999, colonizing seedlings or mature host plants in many environments. Amanita spp.…”
Section: Methodsmentioning
confidence: 99%